Inovações nos laticínios de pequeno e médio porte na região dos Campos Gerais - PR com vistas à manutenção no mercado - Araújo, Alcione Lino de (2014)
This work deals with the innovation in dairy products from small and medium-sized businesses in the region of Campos Gerais - PR. With this approach the state of Parana is highlighting in recent years on the national scene occupying the third place in the production of milk. According to data from the IBGE, the State produced 3,930,428 thousand liters of milk in 2011, responding to 11.7% of national production. It is imperative that environmental sustainability is related to the production of milk, mainly due to the fact that the producer should be aware of the importance of performing an activity that harms the least possible disturbance to the environment. The dynamics of the economy comes from the introduction of innovations by entrepreneurs, through new combinations of factors available, which will result in new products or new processes, replacing the previous structure. Innovation is a fundamental pillar of growth and competitiveness for any company in the competitive market today. This is directly linked to the productivity of the company, improving the process, the solution of problems, in the development of products that will assist in the ability to develop and execute actions successfully. This work has as its general objective, identify the indicators of innovations applied to dairy products from small and medium-sized businesses of General Fields - PR with views maintenance on the market. The methodology used in this work is applied, from the point of view of its nature; qualitative, as well as the problem; exploratory and descriptive, regarding the goals; survey, regarding the technical procedures. As the population and sample, was performed in six dairy products that are in the last era of quality in the months of August and September 2013. As a result it was found that the dairy products from small and mid-sized still has difficulties in incorporating innovation and sustainability in their business chain, now because of the immaturity of their managers regarding the theme, now in the structural conditions and financial, or even, the difficulties of access to technologies coupled with the lack of technical expertise.